Remoção de cromo hexavalente de água utilizando lodo ativado da indústria química como adsorvente - Schommer, Vera Analise (2014)
In the present study, were performed the kinetics, isotherms and thermodynamic treatment of the adsorption of the ions Cr(VI) using adsorbent synthesized from sludge activated as thermally and chemically. The objective was to obtain the kinetic parameters and thermodynamic equilibrium of the process to investigate the behavior of adsorption. The influence of three different temperatures were measured in the adsorption of Cr(VI), with increasing temperature indicated endothermic process. Freundlich, Langmuir / Freundlich and Radke-Prausnitz isotherm best represented the experimental (R2 = 0.99). In the kinetic study, the model that best presented the experimental was the model of Pseudo-Second Order for the three concentrations studied (R2 = 0.99). In thermodynamic treatment Gibbs free energy (ΔG°) revealing only favorable and spontaneous adsorption temperature of 45°C, and the enthalpy (ΔH°) which showed positive values, were analyzed suggesting that the adsorption process can occur by complexation or chemisorption.